Patient portal engagement and diabetes management among new portal users in the Veterans Health Administration. (2nd August 2021) - Zocchi, Mark S; Robinson, Stephanie A; Ash, Arlene S; Vimalananda, Varsha G; Wolfe, Hill L; Hogan, Timothy P; Connolly, Samantha L; Stewart, Maureen T; Am, Linda; Netherton, Dane; Shimada, Stephanie L
Abstract: Objective: The study sought to investigate whether consistent use of the Veterans Health Administration's My Health e Vet (MHV) online patient portal is associated with improvement in diabetes-related physiological measures among new portal users. Materials and Methods: We conducted a retrospective cohort study of new portal users with type 2 diabetes that registered for MHV between 2012 and 2016. We used random-effect linear regression models to examine associations between months of portal use in a year (consistency) and annual means of the physiological measures (hemoglobin A1c [HbA1c], low-density lipoproteins [LDLs], and blood pressure [BP]) in the first 3 years of portal use. Results: For patients with uncontrolled HbA1c, LDL, or BP at baseline, more months of portal use in a year was associated with greater improvement. Compared with 1 month of use, using the portal 12 months in a year was associated with annual declines in HbA1c of -0.41% (95% confidence interval [CI], -0.46% to -0.36%) and in LDL of -6.25 (95% CI, -7.15 to -5.36) mg/dL. Twelve months of portal use was associated with minimal improvements in BP: systolic BP of -1.01 (95% CI, -1.33 to -0.68) mm Hg and diastolic BP of -0.67 (95% CI, -0.85 to -0.49) mm Hg. All associations were smaller or not present for patients in control of these measures at baseline. Conclusions: We found consistent use of the patient portal among new portal users to be associated with modest improvements in mean HbA1c and LDL for patients at increased risk at baseline. For patients with type 2 diabetes, self-management supported by online patient portals may help control HbA1c, LDL, and BP.